Examining the Relationship of Information and Communication Technologies Use and Reading Literacy: A Moderated-Mediation Analysis of Metacognition Across Information and Communication Technologies Use Intensity - Li, Miaoyun; Wang, Meiqian (Frontiers in Psychology, 2022)
The use of information and communication technologies (ICT) is increasingly becoming prevalent among students, both at home and school. While inconsistent results were found for student ICT use and reading literacy, this study attempted to explain these ambiguous links with the moderation of ICT use intensity and mediation of metacognition. Three moderated mediation models for each type of ICT use (at home for entertainment activities and for schoolwork, as well as at school) were analyzed using a Hong Kong sample taken from the Programme for International Student Assessment (PISA) 2018 data pertaining to 5180 15-year-old students from 152 schools. A dynamic effect pattern was found for the links of all ICT use types and reading literacy with the increasing intensity of ICT use, which begins with a positive effect followed by a decrease to less positive, then turns to fluctuating negative and finally ends up with a stable negative effect. But the dominant effect varies across ICT use intensity, which result in different overall effects of three ICT use types. In addition, all three aspects of metacognition showed a profound negative mediation on links of intensive and excessive ICT use with reading literacy, and a less positive mediation for limited ICT use. The metacognition of assessing credibility showed a more important role than summarizing, which was followed by understanding and remembering. In light of the findings, the study recommended that more metacognitive scaffolds should be developed for students with intensive or excessive ICT use, so as to alleviate the side effects of ICT use on their reading literacy.